The Berenstain Bears: old hat, new hat - Berenstain, Stan, 1923-2005; Berenstain, Jan, 1923-2012 (New York : Random House, 1997)
Can the perfect old hat really be replaced by a new one?
"The Berenstain Bears."
On board pages.
Keywords: Hats -- Fiction; Bears -- Fiction; Stories in rhyme